An evaluation of the effects of a lifestyle intervention on eating and physical activity behaviours of urban adolescents in junior public secondary schools in Botswana: a pragmatic randomised controlled trial - Lubinda-Sinombe, Gaonyadiwe (Division of Nursing and Midwifery, 2017)
Background: The prevalence of overweight and obesity is an increasing health problem among adolescents due to unhealthy eating habits and inadequate physical activity. There are 434,000 (21%) adolescents aged 10-19 years in Botswana. The prevalence of overweight among adolescents aged 12-18 years in 2011 in urban private secondary schools in Botswana was 27.1% (192/702) and 13.1% (93/702) in public secondary schools. There is, however, a paucity of data on eating habits and physical activity behaviours and no published evidence was located on the prevalence of overweight among 13-15 year old adolescents in public junior urban secondary schools in Botswana. The determinants of adopting a healthy lifestyle such as information (knowledge), motivation (intentions) and behavioural skills (self-efficacy) have been identified in cross-sectional studies in other countries, but not in Botswana. A culturally suited lifestyle intervention program aimed at motivating adolescents to adopt a healthy lifestyle was not located in the published literature. In the absence of such a lifestyle intervention program for adolescents, the development, implementation and evaluation of the intervention for this study was guided by the Information, Motivation and Behavioural skills (IMBs) model to measure change in eating habits and physical activity behaviours of adolescents in Botswana. Methods: A 2-part study was conducted from 1 November 2015 to18 March 2016. Study One - three research designs were employed: 1) a descriptive design for development of a 3-part questionnaire from existing published literature; 2) a mixed methods approach to validate the prototype questionnaire by determining the index of content validity (n=10 respondents), face validity by cognitive interviewing (n=33 respondents who were scholars), and reliability by test-retest pilot testing (same 33 respondents); and 3) a cross-sectional survey by validated questionnaire of n= 252 respondents' (scholars) eating habits, physical activity behaviours and weight, height and waist circumference to determine the prevalence of overweight. Results from the cross-sectional survey provided baseline data for Study Two. For Study Two a descriptive design was employed to develop and describe a lifestyle intervention movement (LIMO) program followed by a pragmatic randomised controlled trial for implementing and evaluating the effectiveness of the LIMO program (n=25 respondents in the intervention trial arm; n=21 in the control arm from Study One). Null hypothesis: A lifestyle intervention movement (LIMO) program guided by the Information, Motivation and Behavioural skills (IMBs) model will not result in less fatty and sugar intake, an increase in fruit and vegetable consumption, engaging in physical activity 6 or more times a week and doing exercises, a reduction in sedentary behaviour and an increase in nutrition knowledge (P≥0.05). Alternate hypothesis: A lifestyle intervention movement (LIMO) program guided by the Information, Motivation and Behavioural skills (IMBs) model will result in less fatty and sugar intake, an increase in fruit and vegetable consumption, engaging in physical activity 6 or more times a week and doing exercises, a reduction in sedentary behaviour and an increase in nutrition knowledge (P≥0.05). Results: Study One: Good response rate of 95%. The mean age of the respondents was 14.3 years (SD 0.79); mean body mass index (BMI) was 20.1 kg/m2 (SD 3.9) and mean waist circumference score was 71.2 cm (SD 8.71). There were more females in the sample (147/252, 58.3%) than males (105/252, 41.7%). Most of the respondents (153/252, 53.6%) had a low socio-economic status as categorised by the present study. The majority (188/252, 74.6%) had a normal BMI and few (22/252, 8.7%) were underweight. Twenty-seven (10.7%) respondents were overweight, 4/252 (1.6%) were obese and 11/252 (4.4%) were obese with risk. Although few respondents had an abnormal waist circumference (females 17/252, 6.7%; males 14/252, 5.6%) more females (131/252, 52%) than males (90/252, 35.7%) had a normal waist circumference. The most frequently eaten foods were sweets (132/252, 52.4%) and snacks (92/252, (38.1%). Television adverts were sometimes (137/252, 62.3%) considered to be honest. Parents controlled slightly more than half (128/252, 50.8%) of the respondents' food choices whereas peers had little influence (21/252, 8.3%). Of the food types, most ate breakfast comprising of coffee and bread (115/252, 45.6%). Dinner was mostly eaten at home with the whole family (181/252, 71.8%). Of the listed foodstuffs, the majority preferred foods that contained sugar (41/252, 16.3%). Slightly more than half (135/252, 53.6%) of the respondents walked 6 or more times per day each week and more (150/252, 58.7%) reported that they did get exercise. Many intended to change their eating habits (220/252, 87.3%) and physical activity behaviours (143/252, 56.7%) and reported self-efficacy to do so (180/252, 71.4% and 174/252, 69.1% respectively). The majority of respondents (142/252, 56.3%) failed (≤49%) the nutrition knowledge test. The prevalence of overweight was 16.7% (42/252) by body mass index (BMI) and 12.3% (31/252) by waist circumference (WC) respectively. Study Two: There was no statistically significant difference in eating habits between the trial arms (fruit P=0.275, vegetables P= 0.604, sweets P=0.066, fatty foods P=0.402); although there was a difference in sugar consumption this was not statistically significant. There was no statistically significant difference in physical activity (walking 6 times or more a day each week) between trial arms (P=0.267), in doing exercise (P=0.288) and in sedentary behaviour (P=0.362). There was a difference in nutrition knowledge between trial arms but it was not statistically significant (P=0.079). Conclusion and recommendations: Although adolescents had good intentions and self-efficacy to change their eating and physical activity behaviours they engaged in unhealthy behaviours. The LIMO program demonstrated minimal but promising effects on changing behaviours. However further research is needed to determine the best intervention to impact behaviour change.